Terminology and title to chattels: a case against "possessory title" - Rostill, L (Sweet and Maxwell, 2018)
Reflects on uses of the term "possessory title" to identify the interest acquired by an individual who takes possession of another's tangible chattel, and why such an application of the term is a misnomer. Examines four senses in which possessory title is used, the nature of the right acquired, and whether a lesser title is a right to possession. Explains the advantages of using more accurate terminology, such as "general property interest".